Skilful Real‐Time Seasonal Forecasts of the Dry Northern European Summer 2018. Issue 21 (6th November 2019) - Dunstone, Nick; Smith, Doug; Hardiman, Steven; Eade, Rosie; Gordon, Margaret; Hermanson, Leon; Kay, Gillian; Scaife, Adam
Abstract: The Northern European summer of 2018 was the driest for 35 years with resulting impacts on health, agriculture, energy, and water resources. Here we show that this rainfall anomaly was well predicted by a real‐time seasonal forecast. An anticyclonic circulation anomaly was correctly forecast over the North Sea and Scandinavia in 2018 and also in the 1976 record dry summer. In both these exceptionally dry summers, a similar tripole anomaly pattern of North Atlantic sea surface temperatures was present. We perform perturbation experiments that reveal significant circulation, and European rainfall, responses due to changes in the Atlantic meridional temperature gradient. However, consistent with previous work, we find that the model dynamical response is weak relative to that observed and hence large ensembles are required to produce sufficiently skilful predictions. This case study illustrates the potential for the development of summer European climate services. Key Points: Successful real‐time seasonal forecasts for an exceptionally dry Northern European summer in 2018 are shown Similarities to summer 1976 are identified, with a weak circulation signal forecast in both summers Experiments show that a strong tripole pattern of sea surface temperatures in the North Atlantic likely contributed to the forecast dry Northern European summer